Principal Leadership and Supervision as Predictors of Teacher Professional Competency: An Empirical Analysis - Samsilayurni, S; Surismiati, S; Lestari, Winda; Nurlena, Nurlena; Utami, Sri; Walid, Ahmad (Institut Agama Islam Negeri (IAIN) Curup, 2025)
Improving teacher professional competency is a key factor in enhancing the quality of education, and it can be influenced by the leadership and supervisory practices of school principals. This study aims to examine the influence of principal leadership and principal supervision on the professional competence of teachers at SD Muhammadiyah Seberang Ulu 1 Palembang. The research employed a quantitative descriptive approach. The population consisted of all 48 teachers at Muhammadiyah Elementary Schools in Seberang Ulu Palembang, and a saturated sampling technique was used due to the limited population size. Data were collected through validated questionnaires and analyzed using multiple linear regression with SPSS Version 25.0. The findings revealed that: (1) principal leadership has a significant positive influence on teacher professional competence, (2) principal supervision also significantly influences teacher professional competence, and (3) both variables together significantly contribute to teacher professional competency development. The study concludes that effective leadership and supervision by principals are critical predictors of teacher professionalism. This research contributes to the body of knowledge on educational leadership and supports policy and training programs aimed at strengthening school management practices to foster teacher development.